Determinação de plastificantes e seus metabólitos em urina e saliva por HF-LPME-GC/MS para estudos de exposição odontológica - Gabriela Dias Cerqueira (2018)
A hollow fiber liquid phase microextraction method was developed for the determination of bisphenol A (BPA) and phthalate metabolites: Mononisononyl phthalate (MiNP), Monooctyl phthalate (MOP), Monomethyl phthalate (MMP), Monocyclohexyl phthalate (MCHP), Monoisobutyl phthalate (MiBP) Monobutyl phthalate (MBP), Monohexyl phthalate (MEHP), Monobenzyl phthalate (MBzP), Monoethyl phthalate (MEP), Phthalates: Dimethyl phthalate (DMP), Diisononyl phthalate (DiNP), Dibutyl phthalate (DBP) Diethyl phthalate (DEP) in real samples ofurine and human saliva by gas chromatography with mass spectrometry detector (GC / MS). First, three extractive solvents were evaluated: octanol, ethyl octanoate and a mixture of these in the ratio (1: 1, v / v) where the mixture was selected as the acceptor phase. The equilibrium time and the rotation of the agitator used in the extraction were optimized by Doehlert planning and, according to the desirability function, 55 min and2000 rpm were considered the optimum conditions for the extraction. The method developed for the urine analysis showed good results of selectivity, linearity (R2 > 0.913), precision (CV = 0.75 - 17.35 %), low limits of quantification (0.36 - 21.03 g L-1) and detection (0.11 - 6.03 g L-1) for the analytes. The recovery varied between 75 and 105% and the enrichment factor between 421 and 569 %, proving that the optimized method was effective to pre-concentrate the analytes. The method developed was applied in real urine samples from volunteers who had squamous cell carcinoma (SCC) of the mouth (Study Group) and volunteers who did not showed any oral lesion (Control Group). The analytes were found in both groups at different concentrations,and MMP was found at higher concentrations in the study group (322 - 2246 g g -1). A principal component analysis was performed showing that no significant separation occurred between the two groups studied. The chromatographic method developed for saliva showed good selectivity, linearity (R2> 0.900), low detection limits (0.03 - 0.53g L-1) and quantification (0.09 - 1.78g L- 1), good accuracy (CV = 0.86 - 18.68 %) and recovery (83 - 120 %) and high enrichment factors (502 - 719 %). The proposed method was applied in two types of studies. In the first study, saliva samples of volunteers with CCE (Study Group) and without CCE (Control Group) were analyzed, all analytes werefound in both groups except MBzP. As the same as in the urine, MMP was found in higher concentrations in the study group (136 - 539 g L-1) and MEP was found in higher concentrations in the control group (204 - 1351 gL-1). A principal component analysis in saliva samples was also performed and observed a tendency of separation occurring PC2, although the separation was not complete, the results showed that theMCHP, DBP, MBP, MMP e MEHP analytes showed a positive influence on this separation. The second application study for the developed method evaluated the migration of composite resin plasticizers (applied in dental treatments) to the saliva of 8 patients. For this, the saliva of the patient was analyzed before going through the procedure and the saliva of the patient 15 minutes after the exposure occurred. It can be observed that the concentrations of all the analytes increased after the application of theresin, however, statistically there was no significant difference between the concentrations (before and after the process). The results allowed to conclude that both methods developed in this work were efficient for the determination of plasticizers in urine and saliva, making them able to be applied in several ways of monitoring human exposures to these toxic components.